Identifikasi Mikroplastik pada Alga Cokelat (SARGASSUM POLYCYSTUM) dan Alga Hijau (CAULERPA LENTILLIFERA) dari Desa Bintarore Kabupaten Bulukumba - Muh. Fitrah; Sitti Faika; Ahmad Fudhail Majid (Indonesian Journal of Fundamental Sciences, 2026)
Abstract. The purpose of this study is to identify the presence of Microplastics in Brown Algae (Sargassum polycystum) and Green Algae (Caulerpa Lentillifera) from Bintarore Village, Bulukumba Regency. This study is an experimental research with methods such as sample preparation, destruction, density separation, microplastic identification in brown algae and green algae using Olympus CX21 Microscope and Fourrier Transform infrared (FTIR). The results showed that the types of polymers contained in the microplastics found in the brown algae and green algae samples were Polyethylene terephthalate (PET), High density polyethylene (HDPE), and nylon. The abundance of microplastics in brown algae was 18.67 ± 2.08 particles/g and the abundance of microplastics in green algae was 21 ± 2 particles/g. It was concluded that brown algae and green algae from Bintarore village, Bulukumba Regency contained microplastics.Keywords : Microplastics, Brown Algae, Green Algae